Investigation of Hepatitis B Surface Antibody Levels in Adults with Routine Hepatitis B Vaccination in Childhood. - Sehmen, Emine; Yılmaz, Esmeray Mutlu; Oruç, Muhammet Ali (Viral Hepatitis Journal / Viral Hepatit Dergisi, 2023)
Objectives: Recombinant hepatitis B vaccines provide effective and long-term protection. It is not well known whether it reaches protective levels of antibodies in adulthood. In this study, it was aimed to investigate hepatitis B surface antibody (anti-HBs) levels in adults who received routine hepatitis B vaccination in the newborn period and to reveal its change with age. Materials and Methods: The hepatitis B surface antigen (HBsAg) and anti-HBs levels of those who applied to our hospital's health board between 01.01.2017 and 31.12.2021 and were at least 18 years old were evaluated by retrospectively scanned from the board records. Those with anti-HB titers above 10 mIU/mL were considered to have a protective antibody level. Results: The mean age was 20.0±1.5 (18-24). Anti-HBs result was found to be above 10 IU in 1,691 (70.8%) of 2,395 people who were HBsAg negative. In the study, the rate of those who were found to be anti-HBs negative at the age of 18 and 19 was significantly higher than the older age groups, and those with more than 1000 mIU/mL in the 23 and 24 age groups compared to the younger age groups (p<0.001). A significant correlation was found between age and anti-HBs levels (p<0.001; r=0.219). Conclusion: Our study is one of the rare studies measuring the level of hepatitis B vaccine protection for up to 24 years. Our findings demonstrated that the antibody level was found to be above 10 IU in 71% of adults included in the routine hepatitis B vaccination program after birth, and the antibody level did not decrease but rather increased with increasing age.